Intervención social en el borde urbano desde el proceso de la significación cultural (2017)
Due to habitability conditions, there is a need for intervention on the edges of the city. This demands strategies that allow building the imaginary of an inclusive city, under a social gaze and with cultural scenarios that promote signs, codes, and symbols. The inhabitants, from their own recollection and memories, long for a desired environment and contribute to its construction. The territory on the urban edge, the peri-urban space, is made of experiences and memories, in many cases marked by marginality and segregation. This intervention, as a research work, leads to a proposal of design strategies focused on the person, under a qualitative methodology, where the subject carries out the social construction of the territory. As a result, the methodological processes of design are related to listening to the community, creating together with the inhabitants, and delivering a product capable of enhancing memory and identifying the desired urban space, which would generate defensible spaces, without borders or limits, and respect the ideas offered by design that are based on citizen participation.